The German labor market in the Great Recession: Shocks and institutions - Britta Gehrke; Wolfgang Lechtaler; Christian Merkl (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
This paper analyzes Germany's unusual labor market experience during the Great Recession. We estimate a general equilibrium model with a detailed labor market block for postunification Germany. This allows us to disentangle the role of institutions (short-time work, government spending rules) and shocks (aggregate, labor market, and policy shocks) and to perform counterfactual exercises. We identify positive labor market performance shocks (likely caused by labor market reforms) as the key driver for the "German labor market miracle" during the Great Recession. – – Dieses Papier analysiert die außergewöhnliche Entwicklung des deutschen Arbeitsmarktes im Laufe der Großen Rezession in den Jahren 2008 und 2009. Wir schätzen ein allgemeines Gleichgewichtsmodell mit einem detaillierten Arbeitsmarkt mit deutschen Daten ab der Wiedervereinigung. Dieses Vorgehen erlaubt uns die Rolle von verschiedenen Institutionen (Kurzarbeit, Staatsausgaben und Regeln in eben diesen), aggregierten Schocks und politischen Eingriffen zu trennen und deren Wirkungen mit Hilfe von kontrafaktischen Analysen zu quantifizieren. Wir identifizieren positive Schocks auf dem Arbeitsmarkt als wichtigsten Faktor, um das deutsche "Arbeitsmarktwunder" der Jahre 2008 und 2009 zu erklären. Wir argumentieren, dass die Hartz-Arbeitsmarktreformen ursächlich hierfür sind.
Keywords: E24; E32; E62; J08; J63; 330; Great Recession; search and matching; DSGE; short-time work; fiscal policy; business cycles; Germany Keywords